2020
DOI: 10.1590/1806-9061-2019-1169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Broiler Crating Density and Transportation Distance on Preslaughter Losses and Physiological Response During the Winter Season in Punjab, Pakistan

Abstract: A study was conducted to determine the impact of crating density and transportation distance on losses and physiological response of broilers during the winter season. For this, ROSS-308 broilers were crated at three densities (i.e., 10, 12, and 15 birds/crate) in plastic crates and transported in three distances (i.e., 80, 160, and 240 km) during the winter season at 3.6-9.5ºC temperature and 63.3-78.8% relative humidity. Results showed that body weight loss increased significantly with the increase in transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…The triiodothyronine levels which were not different in this study were consistent with the finding of Hussnain et al (2020) on broilers who experienced transportation and feed deprivation. Recent research on buffalo also showed that the cooling method or different seasons did not change triiodothyronine levels (Kumar et al 2019;(Yadav et al 2016).…”
Section: Resultssupporting
confidence: 90%
“…The triiodothyronine levels which were not different in this study were consistent with the finding of Hussnain et al (2020) on broilers who experienced transportation and feed deprivation. Recent research on buffalo also showed that the cooling method or different seasons did not change triiodothyronine levels (Kumar et al 2019;(Yadav et al 2016).…”
Section: Resultssupporting
confidence: 90%
“…Shoaib et al in 2019 observed a high incidence of certain bacterial infections during winter as compared to the summer season [ 25 ]. Moreover, transportation stress on chicks from hatchery to sheds during winter is likely to be associated with the high prophylactic treatments during the first week of winter production cycle [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The negative impact of increased metabolism during the transportation is known to contribute to an increase in body temperature. According to Hussnain et al (2020), the increase in body temperature comes from high metabolic processes, so it produces more metabolic heat when transportation takes place; this metabolic heat affects the increase in body temperature of chickens. This condition can be exacerbated by poor air circulation during transportation in trucks.…”
Section: Body Temperaturementioning
confidence: 99%